Single lithium-ion channel polymer binder for stabilizing sulfur cathodes. Issue 2 (12th October 2019) - Niu, Chaoqun; Liu, Jie; Qian, Tao; Shen, Xiaowei; Zhou, Jinqiu; Yan, Chenglin
Abstract: Lithium–sulfur batteries have great potential for high-performance energy-storage devices, yet the severe diffusion of soluble polysulfide to electrolyte greatly limits their practical applications. To address the above issues, herein we design and synthesize a novel polymer binder with single lithium-ion channels allowing fast lithium-ion transport while blocking the shuttle of unnecessary polysulfide anions. In situ UV–vis spectroscopy measurements reveal that the prepared polymer binder has effective immobilization to polysulfide intermediates. As expected, the resultant sulfur cathode achieves an excellent specific capacity of 1310 mAh g −1 at 0.2 C, high Coulombic efficiency of 99.5% at 0.5 C after 100 cycles and stable cycling performance for 300 cycles at 1 C (1 C = 1675 mA g −1 ). This study reports a new avenue to assemble a polymer binder with a single lithium-ion channel for solving the serious problem of energy attenuation of lithium–sulfur batteries.